Performance analysis of optical CDMA in transmission systems - Biswas, Debobroto; Galib, Saad Yosuf; Mamun, Noor Hossain (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2009.